2021
DOI: 10.5546/aap.2021.eng.106
|View full text |Cite
|
Sign up to set email alerts
|

Excessive screen time is associated with emotional lability in preschool children

Abstract: Introduction. Previous studies have found that excessive screen time or early screen exposure is associated with poor attention, lack of behavioral control, delayed language and deficit in executive functions. The aim of this study was to investigate the relationship between screen time and emotion regulation skills, which is one of the important life components affecting the social relations of children aged 2 to 5 years. Population and methods. This cross-sectional descriptive study was carried out in a univ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 24 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…Also, similar associations were found in this study in terms of PSE by scoring daily screen time according to its volume. Association between lower parental education and excessive screen time is known [ 5 , 20 , 21 ]. Yalcin et al reported a negative correlation between TV viewing time and paternal education [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, similar associations were found in this study in terms of PSE by scoring daily screen time according to its volume. Association between lower parental education and excessive screen time is known [ 5 , 20 , 21 ]. Yalcin et al reported a negative correlation between TV viewing time and paternal education [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Excessive screen time can have a negative impact on children's sleep-wake cycle (when used at night), parent-child interaction and behaviour management. [39][40][41][42] As such, new CAs inform parents about the potential negative impacts of excessive screen time for young children and provide strategies to engage children in alternative activities.…”
Section: Managing Screen Timementioning
confidence: 99%
“…Günaydin et al and Özer et al corroborated this by identifying a significant link between problematic internet use and challenges in emotion regulation [ 42 , 43 ]. Moreover, Oflu et al emphasized that excessive screen time was associated with the negative development of emotional regulation in early childhood [ 44 ]. Echoing these findings, Hidayatullah et al reported that internet-addicted individuals exhibited significant difficulties with emotion regulation [ 45 ].…”
Section: Introductionmentioning
confidence: 99%